Early Marriage Experience (A Phenomenological Study of Gambiran Jember Society): Pengalaman Nikah Dini (Studi Fenomenologi pada Masyarakat Gambiran Jember) - Rachmat Riyanto; Yahya Abdul Azies; Ahmad Fauzan Azhima; Juvan Pabuka Almadjid; Bagas Alfansyah (PT Syamilah Literasi Islami, 2024)
An important experience to learn and understand is the experience of getting married. Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the belief in the Almighty God. Marriage can be carried out if the marriage conditions are met, among the marriage conditions that must be met is meeting the minimum age limit, namely 19 years for men and women. Marriages that take place under this age are called early-age marriages. Gambiran Village is one of the villages in Kalisat District, Jember Regency, East Java. The aim of this research is to determine the experience of early-age marriage in the Gambiran Jember community, the impact of early-age marriage, as well as positive legal, health and Islamic law perspectives on early-age marriage. This research uses a qualitative approach with a phenomenological type of research. The results of this research show that: (1) There are various experiences experienced by perpetrators of early-age marriage in the Gambiran Jember community, which are divided into experiences before and after marriage. (2) Early-age marriage in Gambiran has positive and negative impacts. (3) From the perspective of positive Indonesian law, marriages between minors must apply for marriage dispensation. According to a health science perspective, women are considered to be physically mature when they are 20 years old, so marriages carried out under this age will cause risks to the health of the mother and baby which can lead to death. According to an Islamic legal perspective, there is no age limit as long as the marriage conditions are met.